Eco-Friendly Synthesis of Zirconium Dioxide Nanoparticles from Toddalia asiatica: Applications in Dye Degradation, Antioxidant and Antibacterial Activity - Arumugam Kathirvel; Ramalingam Srinivasan; Sathasivam Harini; Natarajan Ranjith; Govindan Suresh Kumar; Kesavan Lalithambigai; Raji Atchudan; Mohamed A. Habila; Ahmed M. Aljuwayid; Hae Keun Yun (Nanomaterials)
Zirconium dioxide nanoparticles (ZrO2 NPs) have gained significant attention due to their excellent bioavailability, low toxicity, and diverse applications in the medical and industrial fields. In this study, ZrO2 NPs were synthesized using zirconyl oxychloride and the aqueous leaf extract of Toddalia asiatica as a stabilizing agent. Analytical techniques, including various spectroscopy methods and electron microscopy, confirmed the formation of aggregated spherical ZrO2 NPs, ranging from 15 to 30 nm in size, with mixed-phase structure composed of tetragonal and monoclinic structures. UV–visible spectroscopy showed a characteristic band at 281 nm with a bandgap energy of 3.7 eV, indicating effective stabilization by the phytochemicals in T. asiatica. EDX analysis revealed that the NPs contained 37.18 mol.% zirconium (Zr) and 62.82 mol.% oxygen. The ZrO2 NPs demonstrated remarkable photocatalytic activity, degrading over 95% of methylene blue dye after 3 h of sunlight exposure. Additionally, the ZrO2 NPs exhibited strong antibacterial effects, particularly against Gram-negative bacteria such as E. coli, and significant antioxidant activity, with low IC50 values for hydroxyl radical scavenging. In conclusion, the green synthesis of ZrO2 NPs using T. asiatica leaf extract is an effective, eco-friendly method that produces nanoparticles with remarkable antioxidant, antimicrobial, and photocatalytic properties, highlighting their potential for applications in water treatment, environmental remediation, and biomedicine.